Functional characterization of plasmodium falciparum reticulocyte binding like protein homologue 1 (PfRH1) - Yap, Sally Shu Lin (2015)
Human malaria parasites, Plasmodium falciparum, invade human erythrocytes through multiple ligand-receptor interactions. One of the protein families involved in invasion, reticulocyte binding like protein homologues (PfRHs) has been suggested to be involved in host cell selection. Erythrocyte intracellular ATP is essential for merozoite invasion as merozoites fail to invade ATP depleted-erythrocyte, suggesting that ATP is a potential signal in host cell selection. In this work, a novel ATP/ADP binding region (PfNBR) which binds ATP at a higher affinity was identified in PfRH1, a member of PfRHs. IP-coupled photoaffinity labeling assay and Mass spectroscopy data suggest that PfNBR binds nucleotides without the conserved ATP- binding P-loop or A-loop. The determined ATP binding constant of the recombinant PfNBR is in the micromolar (μM) range. Merozoite surface exposure of PfNBR occurs when merozoites are in close contact to erythrocytes, suggesting that PfRH1 could act as an ATP sensor to detect near-membrane environmental ATP released from a deforming erythrocyte during invasion. Epitope mapping of invasion and Ca2+ signaling inhibitory antibodies against Erythrocyte binding domain (EBD) reveals a number of short linear epitopes within the predicted coiled-coils region of the EBD. PfNBR is detected with coiled-coils structures based on the bioinformatic prediction and Circular Dichroism (CD) measurement. Co-presence of PfNBR and EBD in the same processed fragment of PfRH1 implies a close working relationship between these two domains. PfRH1 plays multiple roles along the invasion process including 1) host receptor binding, 2) ATP binding, and 3) signaling transduction but the interplay between these functional roles during invasion remain unclear. A proposed model of the possible molecular mechanism of PfRH1-dependent merozoite invasion may provide us more insights about the invasion mechanisms of malaria parasites and, thus, how these processes might lead to development of new strategies for malaria intervention.